1989
DOI: 10.1002/polb.1989.090270108
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic concepts in the study of size effects in the mechanical strength of highly oriented polymeric materials

Abstract: A study of size effects in the ultimate mechanical properties of crystalline and semicrystalline polymeric materials (fibers, single crystals) is conducted. The concept of size effect and its importance are discussed. A statistical/stochastic approach is adopted and is shown to yield analytical predictions which are at least as accurate as other modeling schemes (mainly based on fracture mechanics theory) previously proposed in the literature. Within this framework, we propose a possible scheme for simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…(Salem et al 1996;Okabe and Hirata 1995), and have also been observed for other quasibrittle materials, e.g. concrete (Weibull 1939) and fibrous materials (Wagner 1989;Schwartz 1987), though not for finegrained perfectly brittle materials at normal laboratory scale.…”
Section: Existing Strength Histograms On Ceramics and Their Fits Withmentioning
confidence: 88%
“…(Salem et al 1996;Okabe and Hirata 1995), and have also been observed for other quasibrittle materials, e.g. concrete (Weibull 1939) and fibrous materials (Wagner 1989;Schwartz 1987), though not for finegrained perfectly brittle materials at normal laboratory scale.…”
Section: Existing Strength Histograms On Ceramics and Their Fits Withmentioning
confidence: 88%
“…The observed strength histograms for ceramics, concrete, and fiber composites (10,30,31) typically exhibit in Weibull scale a kink that separates two segments. The lower segment is a Weibull straight line and the upper one deviates from this line to the right.…”
Section: Macrocrack Growth Law As Consequence Of Subcritical Nanocrackmentioning
confidence: 99%
“…This phenomenon is usually called the size effect and can be understood by two distinct arguments, based either on probability or fracture mechanics. From a probabilistic viewpoint, Weibull (3,4) and Freudenthal (5) proposed a formal link between the probability of occurrence of a critical defect in a solid of (dimensionless) volume, the concentration of defects, and the size (length, area, and volume) of the solid specimen. According to Weibull's model the probability of occurrence of a critical defect (and thus of failure) increases rapidly with increasing size for a given defect concentration.…”
mentioning
confidence: 99%